GOOD LANGUAGE LEARNERS AND THEIR STRATEGIES: AN INSIGHT - Kumaresen Mahalingam; Melor Md. Yunus (Proceedings of The ICECRS, 2016)
The Malaysian Education Blueprint is aimed to ensure every child is proficient in English Language besides Bahasa Malaysia. Thus the English Language syllabus is geared to mould learners to become successful language learners. However, not all learners are capable of being successful language learners despite years of schooling. Therefore, this study aims to investigate language learning strategies used by good language learners in learning English as their second language. To achieve the aim of the study, a questionnaire was used to collect the quantitative data. 30 pupils with good language ability from a rural primary school in Sabah were selected to participate in this study. The findings of the study indicated that different language learners prefer different learning strategies to improve their second language learning. The learning strategies also vary based on the language skills they are learning. The findings of the study are hoped to provide significant impact to the pupils, teachers and curriculum planners to integrate language learning strategies in teaching and learning to assist successful language learning.